2016
DOI: 10.17957/ijab/15.0103
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal Variability of Heavy Metal Concentrations in Soil-rice System and Its Socio-environmental Analysis

Abstract: To cite this paper: Song, Q., S. Jabeen, I.H. Shamsi, Z. Zhu, X. Liu and P.C. Brookes, 2016. Spatio-temporal variability of heavy metal concentrations in soilrice system and its socio-environmental analysis. was used to provide a survey of variations in soil metal concentrations and then interpreted by consideration of soil properties and socio-economical observations. It was concluded that Zn concentration was related to the rapid development of local industry. The socio-environmental factors explained 43.3%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…These observations relate to the findings of the present study in which the exposed tobacco genotypes showed greater MDA content, which indicated high lipid peroxidation. Lead toxicity induces oxidative stress by accumulation of ROS . The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations relate to the findings of the present study in which the exposed tobacco genotypes showed greater MDA content, which indicated high lipid peroxidation. Lead toxicity induces oxidative stress by accumulation of ROS . The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids .…”
Section: Discussionmentioning
confidence: 99%
“…Lead toxicity induces oxidative stress by accumulation of ROS [8,[44][45][46]. The ROS are capable of attacking and oxidizing all types of biomolecules, such as nucleic acids, proteins, and lipids [1].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, heavy metal pollution is one of the most important factors in the short-term anthropogenic impacts on wetlands [18][19][20]. Heavy metals, which affect water quality and the trophic structure and function of communities [18,19,21,22], enter wetland ecosystems in different ways. In contrast to chemical pollutants, heavy metals cannot be removed by natural degradation processes.…”
Section: Introductionmentioning
confidence: 99%
“…49 analyzed the temporal and spatial variation of PTEs in paddy soils polluted by the mining area along the Hengshi River from 2004 to 2012; Song et al . 50 comparative analysis of PTEs changes in paddy soils in Wenling City, Zhejiang Province in 2006 and 2011. Also, some people used space-time-changing methods or constructed models to analyze trends of soil PTEs content.…”
Section: Introductionmentioning
confidence: 99%